The New Image of Indian Girl in Sherman Alexie’s The Search Engine - Mundi Rahayu (Universitas Sanata Dharma, 2022)
The current paper examines the Native American people's identity, especially the main female character's cultural identity in the short story entitled The Search Engine. Sherman Alexie, the author of the story, is a Native American writer who harnesses the Indian identity as one of the main topics. The identity presented in the main character, Corliss, shows the challenges of the stereotypes of Native American girls. For that reason, the paper aims at exploring the new Indian woman’s cultural identity represented in the main character, Corliss, in the short story The Search Engine. The study applies feminist literary criticism that enables the writers to deeply explore the issue of woman's identity among the American native people. The main character, Corliss, shows the new female image identity, in which she can challenge traditional stereotypes of Native American women. Corliss is represented as a highly literate woman, with a lot of reading on English literary works, and has concern on her Indian-ness, which is often incommensurable to her big family’s views. The main character shows the new female image of an Indian girl evidenced in her excellent literacy and attitude toward Indian and White people. She has new consciousness in seeing the Indian men and women and their relation to White people.